2016
DOI: 10.11604/pamj.2016.23.114.7817
|View full text |Cite
|
Sign up to set email alerts
|

Fréquence et facteurs de risque maternels de la mort fœtale in utero à Kamina, République Démocratique du Congo

Abstract: IntroductionLa mort fœtale in utero constitue un problème fréquent dans la pratique obstétricale. Les objectifs de cette étude étaient de déterminer la fréquence et d'identifier les facteurs de risque de la mort fœtale in utero à l'Hôpital Général de Référence de Kamina.MéthodesL’étude était effectuée en deux temps. En premier lieu, une étude descriptive transversale sur 379 accouchements qui avait permis de déterminer la fréquence de la mort fœtale in utero. La détermination des facteurs de risque était faite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The worldwide prevalence of in-utero fetal found by Kubuya in the Democratic Republic of Congo (DRC) [7], Adriamandimbison in Madagascar [8] and Diallo in Guinea, who found rates of 4.9%, 5.2% and 6.9% respectively. On the other hand, it is close to the rate found by Kangulu in the Republic of Congo, 13.9% [1]. In Senegal, a study carried out in a sub-urban area found a prevalence of 3.3% out of 6273 deliveries [9].…”
Section: Frequencysupporting
confidence: 58%
See 2 more Smart Citations
“…The worldwide prevalence of in-utero fetal found by Kubuya in the Democratic Republic of Congo (DRC) [7], Adriamandimbison in Madagascar [8] and Diallo in Guinea, who found rates of 4.9%, 5.2% and 6.9% respectively. On the other hand, it is close to the rate found by Kangulu in the Republic of Congo, 13.9% [1]. In Senegal, a study carried out in a sub-urban area found a prevalence of 3.3% out of 6273 deliveries [9].…”
Section: Frequencysupporting
confidence: 58%
“…For this patient profile, 3 factors are immediately identifiable: referral, multiparity and young age. It has been shown that in Africa, fetal death is more likely to occur in referred patients [1]. Indeed, time is a vital factor in the survival of women with complications.…”
Section: Causes Of Fetal Deathmentioning
confidence: 99%
See 1 more Smart Citation